Thyroid abscess secondary to branchial cleft defect in a child - Francia Rodas, David (2024)
Thyroid abscess is a rare complication because the thyroid gland is resistant to infections. We report an 8-year-old male child who presented with fever, odynophagia, and increased volume in the cervical region. In the left region of the neck, there was a soft erythematous tumor with pain on palpation. Imaging tests reported a collection compatible with thyroid abscess. He required surgical drainage and antibiotics. At seven months of follow-up, the ultrasound shows a branchial cleft defect. Thyroid abscess may be secondary to branchial cleft defect. This rare infection requires drainage in some cases and antibiotics due to endocrine and infectious complications that can compromise the patient's health. As in our case, follow-up is important to identify the cause.